2022
DOI: 10.3390/su14031152
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Synthesis of MIL-101(Cr) for CO2 Gas Adsorption: The Effect of Metal Precursor and Molar Ratio

Abstract: MIL-101(Cr), a subclass of metal–organic frameworks (MOFs), is a promising adsorbent for carbon dioxide (CO2) removal due to its large pore volume and high surface area. Solvent-free synthesis of MIL-101(Cr) was employed in this work to offer a green alternative to the current approach of synthesizing MIL-101(Cr) using a hazardous solvent. Characterization techniques including XRD, SEM, and FTIR were employed to confirm the formation of pure MIL-101(Cr) synthesized using a solvent-free method. The thermogravim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It is observed that Al-BDC-1:3 exhibited a better CO2 adsorption performance compared to Al MOFs at 0.045 mmol/g. This result aligns closely with the observations reported in prior literature studies and the SEM morphology in the previous section [16]. The consistent findings suggest that MOFs with a more refined crystal structure exhibit an increased surface area-tovolume ratio.…”
Section: Effect Of Bdc and Btc Organic Ligand On The Performance Of A...supporting
confidence: 92%
“…It is observed that Al-BDC-1:3 exhibited a better CO2 adsorption performance compared to Al MOFs at 0.045 mmol/g. This result aligns closely with the observations reported in prior literature studies and the SEM morphology in the previous section [16]. The consistent findings suggest that MOFs with a more refined crystal structure exhibit an increased surface area-tovolume ratio.…”
Section: Effect Of Bdc and Btc Organic Ligand On The Performance Of A...supporting
confidence: 92%
“…The factors affecting the adsorption performance of MIL-101(Cr) include not only the temperature, pressure, and sample forms but also the MIL-101(Cr) crystals structure and the synthesis method. Chong et al [ 73 ] proposed a solvent-free method to synthesize MIL-101(Cr). It was found that the best adsorption performance of MIL-101(Cr) was obtained at a Cr:BDC molar ratio of 1:1, with a BET specific surface area of 1110 m 2 g −1 and an adsorption capacity of 18.8 mmol g −1 for CO 2 .…”
Section: Applicationsmentioning
confidence: 99%
“…The expected benzene ring bands were observed between 585.55 and 1600 cm −1 including stretching vibrations (C C) at 1399.97 cm −1 and deformation vibrations (C–H) at 1017.62 cm −1 . The moderate band prevailed at 742.97 cm −1 possibly indicating mono substituted benzene and the band at 585.55 cm −1 is ascribed to Cr–O stretching vibration [ 38 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%